Penguasaan Konsep dan Kemampuan Pemecahan Masalah Fisika Melalui Model Creative Problem Solving (CPS) Berbantuan Mimind - Dua Riong, Maria Bernadetha; Haryono, Haryono; Supriyadi, Supriyadi; Ahmadi, Farid (UNIB Press, 2024)
The orientation of physics learning is to hone reasoning skills, solve mathematical problems from simple to complex problems. The aim of this research was to explain the differences in students' mastery of concepts and problem solving abilities through the Creative Problem Solving (CPS) model assisted by mimind and direct instruction. The research method used was true experiment with a pretest posttest control group design. The total sample of 100 people was selected using cluster random sampling technique. Data were analyzed using the Manova test (Multivariate Analysis of Variance) with a significance level of 0.05. The research results show that the values ​​of Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's largest Root all obtained a value of F = 3.394 with a significance of 0.038 < 0.05. Therefore, it is concluded that there are differences in concept mastery and problem solving abilities between students who use the CPS model assisted by Mimind application and students who use the direct instruction model. The results of this research contribute to the novelty of the CPS model using the mind mapping method through the mimind to the mastery of physics concepts and problem solving abilities.